“Estudio de compatibilidad de cinco ecotipos promisorios de sacha inchi (plukenetia volubilis L.) en la región San Martín-Perú” - Noriega Valera, Hector (2011)
This research seeks to determine a method of controlled pollination and get hybrids (F1), using controlled pollination in five of promising ecotypes inchi sacha (P/ukenetia volubilis L.)., San Martín Region in Peru. "The experiments were realized in the experimental areas of the lnstitute of lnvestigatión of Peruvian Amazon (UAP) - Experiment center "Pucayacu", located to Bello Horizonte 7 km from the city of Tarapoto, in the Banda de Shilcayo district, San Martín Province and Region. The statistical design used was a completely randomized (DCA) with 12 treatments (reciproca! crosses), consisting of five (05) repetitions. The results showed that the 12 treatments (reciproca! crosses) are compatible to oneself, emphasizing the treatment Ta (Q o B x C) with better results in the capsule of 0 (47,51 mm), 0 seeds (20.06 mm) , capsule weight (8,37 g), shell weight (3,74 g), seed weight (4,80 g) and 100 seed weight (109,33 g), respectively, compared with treatments T1 (Ax C o Q ) in the capsule of 0 (34,80 mm), 0 seeds (14,04 mm) of husk weight (2,47 g), and treatment T10 (A x E o Sj?), referred to the weight of capsule (4, 55g), seed weight (2,09 g) and 100 seed weight (52,47 g) respectively. For controlled pollination metods was determined that the metod is the most efficient straw that got the highest number of fruits fertilized with an average of 9,07 fruits I pollinated flowers ten, achieving a 90,70% fertilization compared with the technique of the brush that was an average of 5,52 fruits fertilized I ten pollinated flowers, with a 55,20% fertilization.